Innovative Potential of Digital Economy in the Process of Import Substitution and Environmental Management - KUPRYUSHIN, Aleksandr P. (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.10.7(39).19, 2020)
Each of the stages of import substitution is faced the fact that for formation of a final economic product, it is necessary to develop a procedure for the adoption of identification, which will form the infrastructure according to certain criteria. In this regard, the issue of building infrastructure for the digital economy is becoming very relevant. The novelty of the study is the provision that the innovative potential of the digital economy in the process of import substitution and environmental management can be expanded and tested if the corresponding infrastructure is formed for this. As a basis for infrastructure, integration of the digital economy with macrocycles in the real sector, which provide a change in technological structure, is proposed. This provision is consistent with the fact that each state goes through a technological stage in due time, and all this leads to emergence of a different level of economic isolation and integration. The practical significance of the study is determined by the applicability in the field of environmental management, since the digital economy reduces the overall level of burden on the environment. Each of the elements of the digitalisation of the economy allows calculating the general level of the required environmental resources and ensuring a systematic reduction in their consumption.